Pollen Terminology An illustrated handbook - Hesse, Michael; Halbritter, Heidemarie; Weber, Martina; Buchner, Ralf; Frosch-Radivo, Andrea; Ulrich, Silvia; Zetter, Reinhard (Springer Vienna : Imprint: Springer, 2009)
This handbook is a fully illustrated compendium of glossary terms and basic principles in the field of palynology, making it an indispensable tool for all palynologists. The general chapter on pollen morphology, anatomy, and pollen development deals with essential aspects of palynology. Where appropriate, ambiguous or poorly recognized aspects are explained in greater detail, based on the present state of knowledge in palynology. The terminology section comprises more than 300 widely used terms illustrated with over 1000 high-quality light and/or electron microscope images. It provides a detailed survey of the manifold ornamentation and structures of pollen walls, and offers insights into their stunning aesthetic beauty. Terms are grouped by context to allow easier and faster comparison of similar features. In general, each term is explained on a page of its own, including the definition, plant species, and, if needed, a comprehensive explanation. The use of the terms in LM, SEM or TEM and their assignment to anatomical, morphological and/or functional pollen features are indicated by icons and color coding, respectively. The textual glossary is arranged alphabetically for faster term searches. Key literature sources are mentioned and select cross-references to the general chapter are included for better comprehension.